PENDIDIKAN SEKS DALAM KELUARGA MENURUT PANDANGAN REMAJA - putri, Sukma eka; Natuna, Daeng Ayub; Achmad, Said Suhil (Proceeding 7th International Seminar on Regional Education, 2015)
AbstrackThis study aims to determine the perception of adolescent towards sex education in the family at Tangkerang Tengah village, Pekanbaru . Formulation of the problem in this research is how high the perception of adolescent towards sex education in the family at Tangkerang Tengah village, Pekanbaru? This is a descriptive study with a quantitative approach which aims to describe theresult withfigures. The sampling techniqueusinga quotasamplingtechnique, which is a technique for determininga sampleof thepopulationthathavecertain characteristics untilthe expectations ofthe amount of quota. Data collection techniques inthis study isby using a questionnaire, whichwas 56statement item. The data obtained from respondents whowere 30to samplethe test and 89 for the study. Afte rpollingin the trial, there are six items that are not valid, andthe researchers removed oneby onefactthat is not, so the whole instrument reliably indicated by Cronbach alpha=0.96. The result of the data analysis shows that the perception of adolescent towards sex education in the family from indicator sex differences between men and women relatively high with the value of mean 3.73 and Standard Deviation (SD) 0.74, compared with three other indicator that are the role of sex, the function and need of sex, and personal development. It means that the adolescent feel that sex education is related to sex differnces between men and women is very important for a parents to be given to adolescent.Keywords: sex education, adolescent, family